Demoiselle Signer: an Analysis from Fogel FLOSS Community Framework - Lisboa, Flávio Gomes da Silva (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2022)
This paper aimed to make an analysis of community maturity for Demoiselle Signer, a FLOSS produced by Serviço Federal de Processamento de Dados (Serpro). This research was motivated by criticisms to FLOSS production by Brazilian government entities after a period of support policies. The challenge of this paper was to make a community maturity analysis without an appropriated tool to do it. Then, it was necessary to define a community maturity framework for FLOSS project based on Fogel’s guidelines to create a successful FLOSS project. From what we have named as Fogel’s Framework and with the aid of software called RepoSense, we have analyzed the community maturity of Demoiselle Signer. As it is possible to notice along the paper, the analysis of members is the initial and essential part for investigating the community maturity. From a scale ranging from 0 (zero) to 10, we have determined that Demoiselle Signer has a community maturity equals to 4. This value indicates that Demoiselle Signer is an active community and have some items pointed out by Fogel as desirable features of a FLOSS community infrastructure.